What happened to the exponent rule where (a + b)^2 = a^2 + b^2

Unless... unless that is only for (ab)^2

?

I know that (a + b)(a + b) = a^2 + b^2 + ab + ab

but ugghh this stuff just confuses me.

Printable View

- May 30th 2012, 11:44 AMSplashDamageWhy does (a + b)^2 = a^2 + ab + ab + b^2?
What happened to the exponent rule where (a + b)^2 = a^2 + b^2

Unless... unless that is only for (ab)^2

?

I know that (a + b)(a + b) = a^2 + b^2 + ab + ab

but ugghh this stuff just confuses me. - May 30th 2012, 12:09 PMbob000Re: Why does (a + b)^2 = a^2 + ab + ab + b^2?
(a+b)^2 does not equal a^2 + b^2

(a+b)^2 = (a + b)(a + b) = a^2 + b^2 + ab + ab

(ab)^2= (a^2)*(b^2)